Numerical Study of Integrating Thermal Insulation Local Bio-Sourced Materials into Walls and Roofs for Thermal Comfort Improvement in Buildings in a Tropical Climate - Kokou Dowou; Yawovi Nougbléga; Kokou Aménuvéla Toka; Komi Apélété Amou (Construction Materials)
Thermal insulation is a reliable strategy for achieving optimal thermal comfort in built environments and is among the most effective energy-saving measures. Currently, environmentally friendly insulation materials produced from plant and animal fibers constitute a significant component of the building industry, largely due to their minimal embodied energy and concerns about certain synthetic insulation materials’ potential adverse health effects. The main objective of the present study is to encourage and facilitate the utilization of environmentally friendly thermal insulation materials derived from biological sources, including vegetal and animal fibers, to improve thermal comfort and consequently reduce energy consumption in buildings. The study attempts to simulate the indoor air temperature profiles of a single building constructed using locally sourced materials and insulated in a series of stages with the aforementioned insulation materials. Firstly, insulation is applied exclusively to the roof. Secondly, the insulation is applied to the remaining wall surfaces. Alternatively, the insulation is applied to both the roof and the wall surfaces simultaneously. The objective is to ascertain the optimal combination of bio- and geo-insulating materials to achieve thermal comfort in buildings constructed with local materials in tropical climates. The Gauss-Seidel iterative method was employed to solve the energy equations that had been written on the walls and roof of the building. The equations were then discretized using the nodal method. To ascertain the thermal comfort of the simulated buildings, a comparison was made of the indoor air temperatures. The results of the simulations demonstrated that the utilization of wood fiber, reed panels, and straw bales as insulation materials led to a notable enhancement in comfort levels across all five building types, with an average increase of 17.5%. Among these materials, wood fiber emerged as the most effective insulation option, reducing temperatures by up to 19%. Its integration into the sheet metal-clad Banco building would be particularly advantageous. The findings demonstrate that the simultaneous insulation of walls and roofs with natural fiber thermal insulation materials markedly reduces indoor air and wall temperatures in buildings by up to 19% in comparison to uninsulated walls and roofs.